Preparation method for casting 5A duplex stainless steel and large casting of 5A duplex stainless steel

By adding specific elements and rare earth ferrosilicon alloys to 5A duplex stainless steel, and using air-cooling and solid solution treatment processes, the precipitation of σ phases between metals is avoided, the problems of casting cracking and high scrap rate are solved, and the production efficiency and finished product rate are improved , reducing security risks and costs.

CN119121059AActive Publication Date: 2024-12-13TYCON ALLOY IND (ZHONGSHAN) CO LTD

Patent Information

Application Number
CN202411262987.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The prior art has high scrap rate, low production efficiency and safety risks when casting large castings of 5A duplex stainless steel, and fails to effectively avoid cracking problems caused by the precipitation of the brittle second phase.

Method used

5A duplex stainless steel with specific components is used, including C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, Cr24.0~24.5%, Ni6.0~7.0%, Mo4.0~4.5% , N0.20~0.30%, W0.20~0.30%, Nb0.20~0.30%, Re0.02~0.035%, through intermediate frequency induction furnace smelting, AOD dual refining, rare earth ferrosilicon alloy addition, air-cooling treatment and solid-dissolution Treatment to avoid the precipitation of intermetallic σ phases.

Benefits of technology

It significantly reduces the tendency of the castings to crack, improves the yield and production efficiency, reduces casting defects and safety risks, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121059A_ABST
    Figure CN119121059A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of cast duplex stainless steel, and discloses a cast 5A duplex stainless steel and a preparation method of a large casting of the cast 5A duplex stainless steel, the content of Cr and Mo elements is controlled at the lower limit of the 5A steel standard, meanwhile, W, Nb, Ce and La elements which are refined in structure and reinforced by microalloy are added, and through the coupling effect of the four elements, the temperature interval of brittle phase (sigma phase) precipitation can be avoided, so that the temperature range of the large casting of the cast 5A duplex stainless steel is increased. The method has the advantages that a brittle phase is prevented from being separated out in the slow cooling process of the pump body related large castings, the crack defect in the casting process of the large castings is fundamentally overcome, the casting yield can be increased to 95% or above, and meanwhile, the casting production cost is greatly reduced along with the increase of the process yield and the implementation of cold box opening shakeout; the safety risk in the production process is greatly reduced, and the labor intensity of workers is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal smelting, and in particular relates to a method for preparing a cast 5A duplex stainless steel and a large casting thereof. Background Art

[0002] At present, fast reactors are the preferred reactor type for the fourth generation of advanced nuclear energy systems in the world. The advantage is that they can directly use discarded uranium isotopes. For example, the circulating water pump system of the 600MW fast reactor uses seawater as a heat transfer medium to cool the three-circuit light water. These pump systems, including pump bodies, valves, impellers and other parts, have large sizes (up to tens of meters), complex shapes, and large differences in part cross-sectional dimensions. They are difficult to produce by machining, and are generally cast as a whole. In addition, due to the strong corrosiveness of seawater, the pump system is also subject to fluid corrosion, erosion corrosion and cavitation corrosion. Therefore, the materials of the pump body related parts are required to have high strength and high density, no casting defects, and strong resistance to chloride corrosion and fluid erosion corrosion.

[0003] As the third generation of duplex stainless steel, super duplex stainless steel is characterized by ultra-low carbon, high chromium, high nickel, high molybdenum and high nitrogen. Its excellent mechanical properties and corrosion resistance make it an ideal choice for use in harsh working conditions. Among them, ASTM A890 5A, as a representative of the third generation of duplex stainless steel, has a composition range of: C≤0.030%, Si≤1.0%, Mn≤1.5%, P≤0.040%, S≤0.040%, Cr: 24.0~26.0%, Ni: 6.0~8.0%, Mo: 4.0~5.0%, N: 0.10-0.30%, with excellent comprehensive mechanical properties and cost performance.

[0004] However, with the increase of alloy content, the difficulty of casting 5A super duplex stainless steel increases significantly. During the production process, the brittle second phase represented by the σ phase is easy to be generated at 600-950℃ stage and the brittle decomposition of ferrite at 400-500℃ stage is easy to cause cracking of large castings; in addition, the casting structure is complex, there are many casting heat nodes, the wall thickness of local parts varies greatly, and the uneven wall thickness is easy to cause stress concentration, shrinkage, porosity and other casting defects. The overall casting process is extremely difficult, and the scrap rate of large castings is as high as 70-90% or more.

[0005] The existing preparation process for casting of 5A duplex stainless steel is generally: smelting molten steel with standard composition through medium frequency induction furnace + AOD / VOD dual melting process, then adjusting the temperature of molten steel to 1550-1580℃ for pouring sand mold, waiting for the molten steel to solidify and the sand mold to cool to about 900-1000℃, hot opening and sand removal operation and cutting of the pouring system, and then quickly hoisting the casting for water cooling or cold water spraying to room temperature, and finally adjusting the duplex structure of the casting through 1120-1150℃ solid solution treatment and water cooling. However, hot opening and sand removal of large castings is very dangerous, with high work intensity and low production efficiency. Even so, the scrap rate of large castings is still as high as more than 50%.

[0006] The current mainstream solution focuses on the optimization design of sand casting and cooling systems, such as CN110242781A, which uses optimized sand cores and appropriate cold iron partitions to avoid macroscopic internal stress caused by huge differences in cooling rates in different parts of the parts. There are also considerations of adding a small amount of pure rare earth Ce (CN110242781A) or mixed rare earth elements La, Ce alloy (CN112410675A) to the basic alloy composition to try to obtain better mechanical properties, but all these improved casting processes still require hot unpacking operations, and do not fundamentally solve the problem of brittle cracking caused by the precipitation of a large amount of σ phase during the cooling process of the casting structure. Moreover, previous technologies did not consider the mutual coupling and proportional matching between the added alloy elements.

[0007] In summary, in order to better improve the safe production of large castings of 5A duplex stainless steel, reduce production costs, and increase the yield of large castings, it is urgently necessary to develop a 5A duplex stainless steel suitable for casting and a preparation method that does not require heat unpacking and prevents casting cracking. Summary of the invention

[0008] In order to solve the above technical problems, the object of the present invention is to provide a method for preparing cast 5A duplex stainless steel and large castings thereof, which can not only reduce the casting defects of 5A duplex stainless steel large castings and reduce the scrap rate, but also improve the output rate and finished product rate of large castings, improve production efficiency, and reduce production costs and safety risks.

[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0010] In a first aspect of the present invention, the present invention provides a cast 5A duplex stainless steel, comprising the following components: calculated by weight percentage, C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, S≤0.02%, Cr24.0~24.5%, Ni6.0~7.0%, Mo4.0~4.5%, N0.20~0.30%, W0.20~0.30%, Nb0.20~0.30%, Re0.02~0.035%, and the balance is Fe, wherein the PREN value is: %Cr+3.3%Mo+16%N≥40.

[0011] Preferably, the mass ratio of W to Nb is 1:1.

[0012] Preferably, Re is La+Ce mixed rare earth, wherein the weight ratio of La to Ce is 1:(4-5).

[0013] In a second aspect of the present invention, the present invention provides a method for preparing a large casting of 5A duplex stainless steel, comprising:

[0014] S1. Prepare raw materials according to the mass percentage of each element in the cast 5A duplex stainless steel, sample the remaining raw materials except the rare earth ferrosilicon alloy, and melt them through a medium frequency induction circuit to obtain molten steel, detect the alloy composition of the molten steel through a spectrometer, and adjust it according to the test results until the alloy composition meets the designed composition requirements;

[0015] S2, purifying the molten steel through the AOD double refining process;

[0016] S3, before the molten steel is tapped or in the ladle, rare earth elements are added to the molten steel, and the molten steel is poured into the sand mold;

[0017] S4, air-cooling the molten steel to room temperature, unpacking and removing the sand, cutting off the pouring system, and taking out the casting;

[0018] S5, transferring the casting to a heat treatment furnace for solution treatment;

[0019] S6. After the heat treatment, the furnace is cooled to 1045-1080℃ and then water-cooled after being taken out of the furnace.

[0020] Preferably, in step S1, the smelting temperature is 1650-1680°C.

[0021] Preferably, in step S1, W and Nb elements are added to form a W—Nb master alloy.

[0022] Preferably, in step S3, the rare earth ferrosilicon alloy is pressed into the molten steel, and the mass percentage of rare earth in the rare earth ferrosilicon alloy is 25-30%.

[0023] Preferably, in step S3, the pouring temperature is 1530-1580°C.

[0024] Preferably, in step S5, the solution treatment comprises: placing the casting into a heat treatment furnace at a furnace temperature of 1000°C, keeping the temperature for 30 minutes, heating the casting to 1130-1160°C at a rate of 80-150°C / h, and keeping the temperature for 3-3.5 hours.

[0025] Preferably, in step S6, the water cooling method is circulating water cooling, wherein the circulating water temperature is ≤80°C.

[0026] Beneficial effects:

[0027] The present invention, through the composition design, can completely avoid the precipitation of intermetallic σ phase when the 5A duplex stainless steel is slowly cooled from the liquid phase to room temperature, and the casting structure is fine, which significantly reduces the structure and macro stress of large castings, improves the cracking tendency of large castings, and the casting yield rate can be increased to more than 95%;

[0028] Since the casting process of the present invention does not require hot box sand dropping and high temperature cutting and pouring system, the safety risk of the production process is greatly reduced and the labor intensity of workers is reduced. With the improvement of process yield and the implementation of hot charging furnace process, the casting production efficiency is greatly improved and the cost is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The metallographic structure of the casting after slow cooling in Example 1 of the present invention;

[0030] Figure 2 The scanning electron microstructure of the casting after slow cooling in Example 1 of the present invention;

[0031] Figure 3 The metallographic structure of the casting after solution treatment in Example 1 of the present invention;

[0032] Figure 4 The metallographic structure of the casting after slow cooling in Example 2 of the present invention;

[0033] Figure 5 The scanning electron microstructure of the casting after slow cooling in Example 2 of the present invention;

[0034] Figure 6 The metallographic structure of the casting after slow cooling in Comparative Example 1 of the present invention;

[0035] Figure 7 This is the metallographic structure of the casting after slow cooling in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0037] The invention provides a cast 5A duplex stainless steel, comprising the following components: calculated by weight percentage, carbon (C) ≤ 0.03%, silicon (Si) ≤ 1%, manganese (Mn) ≤ 1.5%, phosphorus (P) ≤ 0.04%, sulfur (S) ≤ 0.02%, chromium (Cr) 24.0-24.5%, nickel (Ni) 6.0-7.0%, molybdenum (Mo) 4.0-4.5%, nitrogen (N) 0.20-0.30%, tungsten (W) 0.20-0.30%, niobium (Nb) 0.20-0.30%, rare earth element (Re) 0.02-0.035%, and the balance iron (Fe), wherein the PREN value is: %Cr+3.3%Mo+16%N≥40.

[0038] Preferably, the mass ratio of W to Nb is 1: 1. More preferably, W and Nb elements are added in the form of a W-Nb master alloy.

[0039] Preferably, Re is La+Ce mixed rare earth, wherein the weight ratio of La to Ce is 1:(4-5). More preferably, the rare earth element is added in the form of rare earth ferrosilicon alloy, wherein the mass percentage of rare earth in the rare earth ferrosilicon alloy is 25-30%.

[0040] Chromium is an important element of stainless steel, and the corrosion resistance of stainless steel increases with the increase of chromium content. However, chromium is also a ferrite-forming element. Adding chromium to steel can promote the formation of ferrite and increase the tendency of forming intermetallic σ phase in stainless steel. Molybdenum can improve the ability of stainless steel to resist pitting and crevice corrosion, especially in a chloride ion environment, where its corrosion resistance is more prominent. Moreover, molybdenum is also a ferrite-forming element, and can also increase the tendency of forming intermetallic σ phase in stainless steel. The present invention controls the content of chromium element to a lower limit of 24.0 to 24.5%, and controls the content of molybdenum element to a lower limit of 4.0 to 4.5%.

[0041] W and Nb are commonly used grain refinement and microalloy strengthening elements, which can improve the toughness and cracking tendency of castings, but W and Nb have high melting points and are easy to form carbides with carbon and become inclusions, so the content cannot be too much. W and Nb can form an infinite solid solution, which helps to enter ferrite. The present invention controls the mass ratio of W and Nb to 1:1, which can significantly inhibit the precipitation of intermetallic σ phase. The present invention designs W and Nb components at a relatively low content of 0.20-0.30%, and adds them in the form of W-Nb master alloy.

[0042] Most importantly, the present invention adds rare earth Ce and La, Ce and La have the effect of surface activity and refinement of organizational elements, and the effect of Ce is stronger than La. The present invention adopts a mixed rare earth ferrosilicon alloy with a lower price. Ce+La enriched in the grain boundary can refine the grains, change the grain boundary state, improve the plasticity and toughness of the steel, and the cracking tendency of the casting. At the same time, Ce+La also has the effect of purification and micro-alloying, which can not only desulfurize and degas, but also change the form, size and distribution of oxides and sulfides in the steel by forming sulfur oxides, which has a very favorable effect on the performance of the steel. However, pure rare earth alloys are easy to oxidize and are not easy to dissolve into the matrix, which will form larger inclusions. Therefore, if the rare earth content is too low, it will not work, and if it is too high, it will easily produce more slag inclusions. The present invention designs the La+Ce composition to be 0.020-0.035%, the ratio of La:Ce to be 1:(4-5), and the rare earth ferrosilicon alloy is pressed into the molten steel or ladle, so that the rare earth is more easily dissolved into the ferrite, thereby significantly inhibiting the precipitation of the σ phase.

[0043] Through the design of each important element of the present invention, the precipitation of intermetallic σ phase can be completely avoided when the molten steel is slowly cooled from the liquid phase to room temperature, and the casting structure is fine, which significantly reduces the structure and macroscopic stress of large castings and improves the cracking tendency of large castings.

[0044] The present invention further proposes a method for preparing large castings based on the above-mentioned cast 5A duplex stainless steel, including preliminary smelting in a medium frequency induction furnace, AOD duplex refining, adding rare earth ferrosilicon alloy, pouring, air cooling, solution treatment and water cooling, and the specific steps are as follows:

[0045] S1. Prepare raw materials according to the mass percentage of each element in the cast 5A duplex stainless steel, sample the remaining raw materials except the rare earth ferrosilicon alloy, and melt them through a medium frequency induction circuit to obtain molten steel, detect the alloy composition of the molten steel through a spectrometer, and adjust it according to the test results until the alloy composition meets the designed composition requirements;

[0046] S2, purifying the molten steel through the AOD double refining process;

[0047] S3, before the molten steel is tapped or in the ladle, the rare earth ferrosilicon alloy is pressed into the molten steel, and the molten steel is poured into the sand mold;

[0048] S4, air-cooling the molten steel to room temperature, unpacking and removing the sand, cutting off the pouring system, and taking out the casting;

[0049] S5, transferring the casting to a heat treatment furnace for solution treatment;

[0050] S6. After the heat treatment, the furnace is cooled to 1045-1080℃ and then water-cooled after being taken out of the furnace.

[0051] Preferably, in step S1, the smelting temperature is 1650-1680°C.

[0052] Preferably, in step S3, the pouring temperature is 1530-1580°C.

[0053] Preferably, in step S5, the solution treatment comprises: placing the casting into a heat treatment furnace at a furnace temperature of 1000°C, keeping the temperature for 30 minutes, heating the casting to 1130-1160°C at a rate of 80-150°C / h, and keeping the temperature for 3-3.5 hours.

[0054] Preferably, in step S6, the water cooling method is circulating water cooling, wherein the circulating water temperature is ≤80°C.

[0055] The technical solution of the present invention is described in detail below with specific embodiments.

[0056] Example 1

[0057] In this embodiment, the designed chemical composition is, by weight percentage, C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, S≤0.02%, Cr24.0~24.5%, Ni6.0~7.0%, Mo4.0~4.5%, N0.20~0.30%, W0.27%, Nb0.27%, Re0.03%, and the rest is Fe. The PREN value: %Cr+3.3%Mo+16%N is 42.1.

[0058] The basic raw materials are prepared according to the chemical composition, wherein W and Nb are added in the form of an intermediate alloy (W:Nb weight ratio is 1:1), and smelted at 1680°C in a medium frequency induction furnace. The preliminary alloy composition is adjusted using a spectrometer until the designed composition requirements are met.

[0059] The molten steel is purified through the AOD double refining process.

[0060] Before the molten steel is tapped or in the ladle, rare earth ferrosilicon alloy (where Ce:La is 4.5:1 and the added amount is 6.4 kg / t molten steel) is pressed into the molten steel, poured at a temperature of 1550°C, and the molten steel is poured into the sand mold.

[0061] Cool to room temperature, unpack and remove sand, remove the pouring system, take out the casting, observe that there are no macro cracks and fine cracks in the casting, and the surface is dense. Cut a small sample from the casting, analyze the alloy composition with a spectrometer, and analyze the rare earth La and Ce in the alloy with inductively coupled plasma emission spectrometry. The results are shown in Table 1. The composition meets the standard requirements, and the PREN value is 42.1. Its metallographic structure is as follows Figure 1As shown in the figure, the as-cast structure is fine, with only austenite and ferrite structures, and the precipitated σ phase is basically not observed. It can only be seen through the enlarged scanning electron microscope (such as Figure 2 ), only a very small amount of σ phase can be observed. Analysis shows that the σ phase content is only about 0.5%, indicating that the 5A steel with this composition can completely inhibit the precipitation of σ phase during the slow cooling process, thereby avoiding the cracking of the casting.

[0062] The casting was transferred to a heat treatment furnace, and placed in a heat treatment furnace at a furnace temperature of 1000°C. After being kept at this temperature for 30 minutes, the temperature was increased to 1150°C at a rate of 150°C / h and kept at this temperature for 3.5 hours.

[0063] After the heat treatment, the furnace is cooled to 1080℃ and then water-cooled. The water cooling is circulating water cooling with a water temperature of ≤80℃. The impeller castings produced have dense structure and meet the requirements of ASMEⅧ, DIV.1, APP.7 after penetration inspection. Small samples are cut from large castings for metallographic structure observation, such as Figure 3 As shown, its structure is composed of austenite and ferrite, of which the ferrite content is 54.4%. According to the ASTM A370 method, the sample was tested for mechanical properties. Its tensile strength was 767MPa, its elongation was 31%, its low temperature (-46°C) impact resistance was 107AKV / J, and its average hardness was 247HB, showing excellent mechanical properties. According to ASTM G48-3 method A, a 24h crevice corrosion test was carried out in a 50°C, 6% FeCl3 solution. The loss was 0.0016g, there was no pitting corrosion, and the corrosion rate was 0.471g / m 2 , excellent corrosion resistance.

[0064] Example 2

[0065] In this embodiment, the designed chemical composition is, by weight percentage, C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, S≤0.02%, Cr24.0~24.5%, Ni6.0~7.0%, Mo4.0~4.5%, N0.20~0.30%, W0.22%, Nb0.22%, Re0.02%, and the rest is Fe.

[0066] The basic raw materials are prepared according to the chemical composition, wherein W and Nb are added in the form of an intermediate alloy (W:Nb weight ratio is 1:1), and smelted at 1650°C in a medium frequency induction furnace. The preliminary alloy composition is adjusted using a spectrometer until the designed composition requirements are met.

[0067] The molten steel is purified through the AOD double refining process.

[0068] Before the molten steel is tapped or in the ladle, rare earth ferrosilicon alloy (where Ce:La is 5:1 and the added amount is 4.2 kg / t molten steel) is pressed into the molten steel, poured at a temperature of 1560°C, and the molten steel is poured into the sand mold.

[0069] Cool to room temperature, unpack and remove sand, remove the pouring system, take out the casting, observe that the casting has no macro cracks and fine cracks, and the surface is dense. Cut a small sample from the casting, analyze the alloy composition with a spectrometer, and analyze the rare earth La and Ce in the alloy with inductively coupled plasma emission spectrometry. The results are shown in Table 1. The composition meets the standard requirements, and the PREN value is 41.7. Its metallographic structure is as follows Figure 4 As shown in the figure, it can be seen that the cast structure is relatively fine, basically only austenite and ferrite structure, only a small amount of precipitated σ phase, only through the magnified scanning electron microscope (such as Figure 5 ), only a very small amount of σ phase can be observed. Analysis shows that the σ phase content is only about 1%, indicating that the composition 5A steel can completely inhibit the precipitation of σ phase during the slow cooling process, thereby avoiding the cracking of the casting.

[0070] The casting was transferred to a heat treatment furnace, and placed in a heat treatment furnace at a furnace temperature of 1000°C. After being kept at this temperature for 30 minutes, the temperature was increased to 1130°C at a rate of 80°C / h and kept at this temperature for 3 hours.

[0071] After the heat treatment, the furnace is cooled to 1080℃ and then water-cooled. The water cooling is circulating water cooling with a water temperature of ≤80℃. The castings produced have dense structure, excellent mechanical properties and corrosion resistance. Small samples are cut from large castings, and their structure consists of austenite and ferrite, with a ferrite content of 55.1%.

[0072] Comparative Example 1

[0073] In this comparative example, the designed chemical composition is, by weight percentage, C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, S≤0.02%, Cr24.0~24.5%, Ni6.0~7.0%, Mo4.0~4.5%, N0.20~0.30%, and the rest is Fe.

[0074] The basic raw materials are prepared according to the chemical composition, smelted at 1680℃ in a medium frequency induction furnace, and the preliminary alloy composition is adjusted using a spectrometer until the designed composition requirements are met.

[0075] The molten steel is purified through the AOD double refining process.

[0076] The molten steel is poured into the sand mold at a temperature of 1580°C.

[0077] After air cooling to room temperature, the box was unpacked and the sand was removed, the pouring system was removed, and the casting was taken out. It was observed that the casting had macroscopic cracks. The casting was unqualified and no subsequent heat treatment process was performed. A small sample was cut from the crack-free part of the casting, and the alloy composition was analyzed by spectrometer. The rare earth La and Ce in the alloy were analyzed by inductively coupled plasma emission spectrometry. The results are shown in Table 1. The composition meets the standard requirements and the PREN value is 41.1. Its metallographic structure is as follows Figure 6 As shown in the figure, its as-cast structure is coarse, there are more σ precipitation phases at the grain boundaries, and they form a network, and the content of σ precipitation phase is as high as 28.5%. This is similar to the metallographic structure of general 5A duplex stainless steel castings.

[0078] Comparative Example 2

[0079] In this comparative example, the designed chemical composition is, by weight percentage, C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, S≤0.02%, Cr24.0~24.5%, Ni6.0~7.0%, Mo4.0~4.5%, N0.20~0.30%, W0.5%, Nb0.20%, Re0.012%, and the rest is Fe.

[0080] The basic raw materials are prepared according to the chemical composition, where W-Nb is added in the form of an intermediate alloy (W:Nb weight ratio is 2.5:1). The alloy is smelted at 1650°C in a medium frequency induction furnace, and the preliminary alloy composition is adjusted using a spectrometer until the designed composition requirements are met.

[0081] The molten steel is purified through the AOD double refining process.

[0082] The molten steel is poured into the sand mold at a temperature of 1550°C.

[0083] After air cooling to room temperature, the box was unpacked and the sand was removed, the pouring system was removed, and the casting was taken out. Macroscopic cracks were observed in the casting, and the casting was unqualified, so no subsequent heat treatment process was performed. A small sample was cut from the crack-free part of the casting, and the alloy composition was analyzed by spectrometer, and the rare earth La and Ce in the alloy were analyzed by inductively coupled plasma emission spectrometry. The results are shown in Table 1. The composition meets the standard requirements, and the PREN value is 42.3. Its metallographic structure is shown in Table 1. Figure 7 As shown in the figure, it can be seen that the as-cast structure is relatively fine, but there are many blocky σ precipitation phases, and the content of σ precipitation phase is as high as 24.7%, which is the main reason for the macroscopic cracking of the casting.

[0084] Table 1 Casting composition of the embodiments and comparative examples (mass percentage %)

[0085]

[0086] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A cast 5A duplex stainless steel, characterized in that: The invention comprises the following components: calculated by weight percentage, C≤0.03%, Si≤1%, Mn≤1.5%, P≤0.04%, S≤0.02%, Cr24.0~24.5%, Ni 6.0~7.0%, Mo4.0~4.5%, N0.20~0.30%, W 0.20~0.30%, Nb 0.20~0.30%, Re 0.02~0.035%, and the balance is Fe, wherein the PREN value is: %Cr+3.3%Mo+16%N≥40.

2. The cast 5A duplex stainless steel according to claim 1, characterized in that: The mass ratio of W to Nb is 1:

1.

3. The cast 5A duplex stainless steel according to claim 1, characterized in that: Re is a mixed rare earth of La+Ce, wherein the weight ratio of La to Ce is 1:(4-5).

4. A method for preparing a large casting of 5A duplex stainless steel, characterized in that: The method of preparing a large casting using the cast 5A duplex stainless steel as claimed in any one of claims 1 to 3 comprises: S1. Prepare raw materials according to the mass percentage of each element in the cast 5A duplex stainless steel, sample the remaining raw materials except the rare earth elements and melt them through a medium frequency induction circuit to obtain molten steel, detect the alloy composition of the molten steel through a spectrometer, and adjust according to the test results until the alloy composition meets the designed composition requirements; S2, purifying the molten steel through the AOD double refining process; S3, before the molten steel is tapped or in the ladle, rare earth elements are added to the molten steel, and the molten steel is poured into the sand mold; S4, air-cooling the molten steel to room temperature, unpacking and removing the sand, cutting off the pouring system, and taking out the casting; S5, transferring the casting to a heat treatment furnace for solution treatment; S6. After the heat treatment, the furnace is cooled to 1045-1080℃ and then water-cooled after being taken out of the furnace.

5. The preparation method according to claim 4, characterized in that: In step S1, the melting temperature is 1650-1680°C.

6. The preparation method according to claim 4, characterized in that: In step S1, W and Nb elements are added to form a W—Nb master alloy.

7. The preparation method according to claim 4, characterized in that: In step S3, rare earth elements are pressed into the molten steel in the form of rare earth ferrosilicon alloy, wherein the mass percentage of rare earth in the rare earth ferrosilicon alloy is 25-30%.

8. The preparation method according to claim 4, characterized in that: In step S3, the pouring temperature is 1530-1580°C.

9. The preparation method according to claim 4, characterized in that: In step S5, the solution treatment includes: placing the casting into a heat treatment furnace at a furnace temperature of 1000°C, keeping the temperature for 30 minutes, heating the temperature to 1130-1160°C at a rate of 80-150°C / h, and keeping the temperature for 3-3.5 hours.

10. The preparation method according to claim 4, characterized in that: In step S6, the water cooling method is circulating water cooling, wherein the circulating water temperature is ≤80°C.

Citation Information

Patent Citations

  • Super duplex stainless steel 5A material butterfly valve and manufacturing method

    CN110242781A

  • Rare earth double-phase corrosion-resistant cast stainless steel and manufacturing method thereof

    CN112410675A

  • High temperature oxidation resistant ferrite heatproof stainless steel and manufacturing method thereof

    CN105506489A

  • Casting method for impeller made of super duplex stainless steel 5A material

    CN107309405A

  • Niobium-titanium composite reinforced duplex stainless steel and preparation method thereof

    CN114395739A

Cited By

  • An industrial method for preparing a high-strength, high-ductility cast austenitic stainless steel support.

    CN122669288A